Analyzing the effects of urban sprawl on the physical environment in the case of Kyrenia - Shirkhanloo, Nina (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The formation of urban planning can be dating back to the primary cities in previous centuries. Throughout the last decades, urban population has been rapidly increased due to urbanization in developing countries. Excessive growth of population due to urbanization led to upward growth of cities, which as consequence cities missed their realms and boundaries and produced variety of urban forms that took a little consider of their affects upon the environment. Thus, this century experienced the miracle of urban sprawl as the initial primary urban form. The urban sprawl and the expansion of urban areas are the concerns of today’s cities due to social, environmental and economic negative impacts that has in the cities. According to these impacts, it is believed that urban sprawl demonstrates a threat for urban sustainability, since it indicates high level of land, water and energy consumption, as well as increase pollutants and wastes. In the today’s world the best way to implement sustainability is the urban development and overcoming the consequences of rapid urban planning such as urban sprawl. Hence, sustainable urban forms would be a solution for this phenomenon to achieve sustainability in all three dimensions in the contemporary cities. Accordingly, the focus of this study is analyzing the types and costs of urban sprawl in Kyrenia’s physical environment. The problem area and field study of this research will be East side of kyrenia city along coastal line in the North Cyprus. Based on initial discussion, the thesis will have five chapters. In the first chapter, the introductory part will be given. In the second chapter, this study reviews urban sprawl within coastal line by concentrating on sustainable urban form. Hence, this research first gives knowledge about definition, types and effects/costs of sprawl on the physical, natural and social environmental of the cities then in the third chapter reviews the concept of sustainability and identified sustainable urban forms. Afterwards, in chapter four all dimensions of urban sprawl on the east side of Kyrenia along coastal line as case study and problem area will be measured in order to achieve the main aim of this thesis which is to analyze the types and costs of urban sprawl on Kyrenia city and to evaluate the physical problems in line with the sustainability. Finally, the effects of sprawl in the case study will be presented with special reference to coastal area and then the most suitable urban form will be suggested for eliminating these negative effects of sprawl in the city. Legal and administrative failure including street and building regulations (cap 96), 1993 environmental conservation plan Notice and many notices up to now; as well as Annan Plan (2002) are factors that accelerate urban sprawl in Kyrenia. The methodology of this study is based on qualitative technique. The data evaluation will be collected through literature survey and field studies. Accordingly, literature survey includes reviews on the sources, which are about the subject/keywords of the thesis. Field study will be done in Kyrenia along the coast area. It will consist of observations, photographs, maps, analyzing of the land-use changes, urban pattern and population growth. According to analysis, leapfrog development of urban sprawl in Kyrenia will be act as a factor for future likelihood environmental problems such as high energy and land consumption, loss of agricultural land and loss of green areas. To put in the nutshell, the data which examined and evaluated in the last part will be concluded to suggest smart growth for future expansion of Kyrenia in order to achieve achieve sustainability in the urban development which is the main aim of this study. Keywords: Urban Sprawl, Sustainable Urban Forms, Leapfrog Development, Smart Growth, Kyrenia. ………………………………………………………………………………………………………………………… ÖZ: Kent planlaması ilk yerleşimlerin oluştuğu yüzyıllara dayanan bir olgudur. Son on yıllar boyunca, kentleşmenin etkisiyle tüm dünyada kentlerin demografik, ekonomik ve mekansal yapılarında önemli değişimler meydana gelmiştir . Kentleşmenin etkisiyle oluşan aşırı nüfüs artışı kentlerin büyümesine, sınırlarının değişmesine ve farklı tiplerde kentsel biçimlere sahip olmalarına neden olmuştur. Bundan dolayı, bu yüzyılda kentlerin büyümesi kentsel saçaklanma şeklinde olmaktadır. Kentsel saçaklanma ve genişleme bugünün kentlerinde olumsuz yönde değişen sosyal, çevresel ve ekonomik yapılar sonucu ortaya çıkmaktadır. Toprağın, suyun ve enerjinin aşırı tüketimi, kirliliğin ve çöplerin artması gibi olumsuz etkiler nedeni ile kentsel saçaklanma, kentsel sürdürülebilirlik için bir tehdit oluşturduğu tartışılmaktadır. Bugünün dünyasında kentlerde sürdürülebilirliği sağlamanın en iyi yöntemi hızlı kentsel gelişmenin ve dolayısıyla kentsel saçaklanmanın olumsuz sonuçlarının üstesinden gelmektir. Bundan dolayı, sürdürülebilir kentsel biçimler, kentlerin ekonomik, sosyal ve çevresel yapılarında sürdürülebilirliği elde etmek için çözüm olabilmektedir. Bu çalışmada Kuzey Kıbrıs’ın sahil kenti olan Girne ‘nin doğu sahil şeridi çalışma alanı olarak seçilmiştir. Bu bağlamda, tez kapsamında Girne kenti doğu sahil şeridindeki kentsel saçaklanmanın çeşitleri ve kentlere etkileri araştırılacak ve daha sonra sürdürülebilir kentsel biçimler tarışılacaktır. Buna bağlı olarak, çalışma beş bölümden oluşmaktadır. Birinci bölümde, girizgah verilmiştir. İkinci bölüm tez araştırmasının kavramsal ve kuramsal kısmını oluşturmaktadır. Burada kentsel saçaklanma, tipleri, nedenleri ve etkileri yanında kentsel saçaklanmanın farklı ölçme/değerlendirme metodları tartışılmaktadır. Kentsel saçaklanmaya bir çözüm olarak görülen sürdürülebilir kentsel biçimler ise üçüncü bölümde gözden geçirilmektedir. Dördüncü bölümde mevcut yasal ve idari yapıdaki yetersizlikler, sıkça değişen yasalar ve 2002 yılında Anan Planı sonucu hızlı, kontrolsuz ve dağınık gelişen bir yapıya sahip olan Girne kentin’deki kentsel saçaklanmanın biçimi ve çevresel etkileri ortaya konmaktadır. Sonuç, öneriler ve bu çalışmanın devamı niteliğinde olabilecek çalışmalar dile getirilmiştir. Bu çalışmada nitel ve nicel araştırma teknikleri kullanılmıştır. Konu ile ilgili literature ve saha çalışması yapılmıştır. Yaplan analizler sonucunda, Girne kentinin doğu sahil şeridindeki kentsel saçaklanmanın, sıçrayarak büyüme şeklinde olduğu tespit edilmiştir. Bu büyüme şekline gore ise yüksek oranda arazi ve enerji kullanımı/tüketimi, tarımsal arazi ile yeşil alan kaybı yaşandığı gözlemlenmiştir. Buna göre, daha düzenli ve kaynakları fazla tüketmeden yayılması için akıllı büyüme olarak gelişmesi gerektiği önerilmiştir. Anahtar Kelimeler: Kentsel Saçaklanma, Sürdürülebilir Kentsel Biçimler, Sıçrayarak Büyüme, Akıllı Büyüme, Girne.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Assoc. Prof. Dr. Beser Oktay Vehbi.
Keywords: Architecture; Urban Design; Urban Landscape Architecture - Kyrenia (Cyprus, North); City Planning - Urpan Policy - Kyrenia (Cyprus, North); Urban Sprawl, Sustainable Urban Forms, Leapfrog Development, Smart Growth, Kyrenia